Sentiment analysis for Bengali newspaper headlines - Hossain, Mohammad Samman; Jui, Israt Jahan; Suzana, Afia Zahin (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.